2012
DOI: 10.1063/1.3687922
|View full text |Cite
|
Sign up to set email alerts
|

Open-system Kohn-Sham density functional theory

Abstract: A simple model for electron transport through molecules is provided by the source-sink potential (SSP) method [F. Goyer, M. Ernzerhof, and M. Zhuang, J. Chem. Phys. 126, 144104 (2007)]. In SSP, the boundary conditions of having an incoming and outgoing electron current are enforced through complex potentials that are added to the Hamiltonian. Depending on the sign of the imaginary part of the potentials, current density is generated or absorbed. In this way, a finite system can be used to model infinite molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…Dissociative recombination via autoionizing states is important in interstellar chemistry (4). Resonances are also involved in condensed-phase processes, e.g., in radiolysis and damage to DNA by slow electrons (5,6), single-molecule electronics (7), and plasmonic catalysis (8,9) (see the sidebar titled Plasmonic Catalysis).…”
Section: Introduction: What Is a Resonance?mentioning
confidence: 99%
“…Dissociative recombination via autoionizing states is important in interstellar chemistry (4). Resonances are also involved in condensed-phase processes, e.g., in radiolysis and damage to DNA by slow electrons (5,6), single-molecule electronics (7), and plasmonic catalysis (8,9) (see the sidebar titled Plasmonic Catalysis).…”
Section: Introduction: What Is a Resonance?mentioning
confidence: 99%
“…[35][36][37][38] The method of source-sink potentials is a second example where the Hamiltonian of the finite system is augmented by source and sink terms that serve to inject and absorb electrons near the physical boundaries of the finite system. [39][40][41][42][43] One of the earliest time-dependent approaches developed along these lines suggested that the explicit calculation of leads' self-energies can be avoided by approximating them with complex absorbing potentials. [44][45][46] Here, the timedependent response of the finite system to an external electric field perturbation 44,45 or local edge potentials 46 is simulated and the excited electrons are absorbed near the boundaries, thus dissipating the excess energy that they carry and avoiding back-scattering into the system.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, 18 the SSP method had only been implemented for Hückel models 14,19,20,21,22 This is because the determinantal equation reduces to an n L × n L determinant for such models; n L is the number of open channels on the left, the source of the incoming wave. For incoming waves on the right, the determinant is n R × n R .…”
Section: The Source-sink Potential Methodsmentioning
confidence: 99%
“…The zeroth-order reference system is the isolated neutral molecule for which the atomic charge distribution is given by (18) …”
Section: Model Of Molecular Charging and Polarization Accompanying Nomentioning
confidence: 99%